Lessons of healthy lifestyle with the Science in the Kitchen - Lippi, Donatella; Sofi, Francesco; Casini, Alessandro; Abbate, Rosanna; Gensini, Gian Franco (Progress in Nutrition, 2014)
Lifestyle behaviours such as healthy diet, physical activity and abstinence from tobacco smoking are widely known to be significantly associated with reduced occurrence of chronic degenerative diseases. Actually, a growing interest on wellness and lifestyle-related habits for prevention of disease and maintenance of good health status has been recently reported. A holistic approach to the health, which include not only risk factor’s management but also some lifestyle measures as sleep quality, meditation and stress are placing a relevant role in the recent preventive medicine. Nevertheless, the interest on these lifestyle behaviours is something that comes from the ancient Medicine, since one of the most famous attributed to Hippocrates statements is “if we were able to furnish the optimal dose of nutrients and physical activity we would have found the right way for health”. Aim of this paper is to highlight the contribution of Pellegrino Artusi, who, in 1891 published his masterpiece “Science in the Kitchen and the Art of Eating Well”. Some statements reported in this book need to be restored and remembered in the light of this increasing interest on lifestyle habits for the prevention of disease in the modern society.